Medina by the bay: scenes of Muslim study and survival - Kashani, Maryam (Duke University Press, 2023)
"In Medina by the Bay Maryam Kashani examines how multiracial Muslim communities in the San Francisco Bay area forge alternate ways of surviving and flourishing in the face of colonial racial capitalism. Drawing on ethnographic fieldwork at a Muslim liberal arts college, mosque communities, and prison courtyards, Kashani outlines how contemporary Islam emerges from the specificities of the Bay Area. She demonstrates that sociopolitical forces and geopolitical agendas ranging from the Black Power movement and state surveillance to Silicon Valley and gentrification shape Muslim ways of knowing and being. Throughout, Kashani weaves vignettes written as cinematic scenes in a screenplay that juxtapose different times, figures, places, and events in ways that highlight the Bay Area's racial, carceral, and imperial logics. Theorizing the Medina by the Bay as a microcosm of the socioeconomic, demographic, and political transformations in the twentieth and twenty-first centuries, Kashani illustrates the ways Islam offers a liberatory and abolitionist theory, theology, and praxis for non-Muslims engaged in social struggle around the world"--